CORRELATION ANALYSIS OF AGRONOMIC CHARACTERS AND GRAIN YIELD OF RICE FOR TIDAL SWAMP AREAS - Hairmansis, Aris; Kustianto, Bambang; Suwarno, Suwarno (Indonesian Agency for Agricultural Research and Development - MOA, 2010)
Development of rice varieties for tidal swamp areas is emphasized on the improvement of rice yield potential in specific environment. However, grain yield is a complex trait and highly dependent on the other agronomic characters; while information related to the relationship between agronomic characters and grain yield in the breeding program particularly for tidal swamp areas is very limited. The objective of this study was to investigate relationship between agronomic characters and grain yield of rice as a basis for selection of high yielding rice varieties for tidal swamp areas. Agronomic characters and grain yield of nine advanced rice breeding lines and two rice varieties were evaluated in a series of experiments in tidal swamp areas, Karang Agung Ulu Village, Banyuasin, South Sumatra, for four cropping seasons in dry season (DS) 2005, wet season (WS) 2005/2006, DS 2006, and DS 2007. Result from path analysis revealed that the following characters had positive direct effect on grain yield, i.e. number of productive tillers per hill (p = 0.356), number of filled grains per panicle (p = 0.544), and spikelet fertility (p = 0.215). Plant height had negative direct effect (p = -0.332) on grain yield, while maturity, number of spikelets per panicle, and 1000-grain weight showed negligible effect on rice grain yield. Present study suggests that indirect selection of high yielding tidal swamp rice can be done by selecting breeding lines which have many product tive tillers, dense filled grains, and high spikelet fertility.